Hypnosis and Emancipated Imagination - Sabolius, Kristupas (Problemos, 2016)
This paper explores the hypnotic induction as related to the plastic power of creative imagination in contemporary artistic tendencies. Stemming from the concept of manipulation, present already in Mesmer’s, Charcot’s and Freud’s accounts of hypnosis, the analysis aims to provide a few cases of alternative use of a trance-inducing practices. Focusing on Raimundas Malašauskas’s, Marcos Lutyens’s, Catherine Contour’s and Joris Lacoste’s projects in conceptual art, dance, and theatre, as well as drawing parallels with theoretical tools provided by Immanuel Kant, Bernard Stiegler, Jacques Rancière and François Roustang, it discloses the emancipatory role of hypnosis. Conceived as the technique of rhythmical modulation, providing the disensus in the distribution of the sensible, artistic hypnosis could be considered, along the lines of Roustang, as “paradoxical wakefulness” and emancipated form of imagination, which allows to esape mental clichés as well as abuse of authority and manipulation.
Keywords: hypnosis; imagination; dream; wakefulness; disensus